Islamic spirituality and civilization - Omer, Spahic (Dar al-Wahi, 2019)
This book is a compilation of articles on various issues relating to the Islamic spirituality and civilization. The articles are written in essay forms and are meant to be as educating and enriching, as thought-provoking and challenging. They span a wide range of topics from the Islamic belief system, values, ethics, worldview, society, history, epistemology and education, to tradition versus modernity dialectics, general development, sustainability, art and architecture. The book thus represents a mosaic of ideas subtly interrelated and woven into a unified total that clearly shows how close to each other Islamic spirituality and civilization are. There are two main objectives of the book. First, to exhibit the true meaning of some foremost aspects of Islamic spirituality and Islamic civilization, and how they are inextricably interconnected in such a way that the former functions as the foundation, essence and moral fiber of the latter. Second, to clarify, and possibly eliminate, some of the enduring misconceptions about Islam and its civilization, at the conceptual, epistemological and practical levels. With its integrated as well as interdisciplinary approach and method, this book intends to contribute towards that direction; that is, to participate in explaining the true sense and value of Islamic civilization and how amalgamating itself with Islamic spirituality is the only way forward.